2008
DOI: 10.1080/19396360701876815
|View full text |Cite
|
Sign up to set email alerts
|

A Reverse Transcriptase-Dependent Mechanism Plays Central Roles in Fundamental Biological Processes

Abstract: This review summarizes emerging evidence that LINE-1 (Long Interspersed Nuclear Elements) -encoded reverse transcriptase (RT) regulates fundamental biological processes. Earlier studies showed that sperm cells can be used as vectors of both exogenous DNA and RNA molecules in spermmediated gene transfer assays. During these studies, a sperm endogenous RT activity was identified, which can reverse-transcribe exogenous RNA directly, or DNA molecules through sequential transcription and reverse transcription. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 56 publications
0
33
0
5
Order By: Relevance
“…These experiments have brought about very important but overlooked findings. Specifically, they demonstrate that the functional knockdown of L1 expression via L1-specific RNA interference (RNAi) and the inhibition of RT both independently result in the same biological outcomes [26,28]. This suggests that both transcription and reverse transcription of L1s are links in the same chain in these cell systems.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…These experiments have brought about very important but overlooked findings. Specifically, they demonstrate that the functional knockdown of L1 expression via L1-specific RNA interference (RNAi) and the inhibition of RT both independently result in the same biological outcomes [26,28]. This suggests that both transcription and reverse transcription of L1s are links in the same chain in these cell systems.…”
Section: Reviewmentioning
confidence: 99%
“…This suggests that numerous L1s may regulate transcription and DNA replication through their involvement in the establishment of the three-dimensional (3D) structure of chromatin. On the other hand, abundantly expressed FL-L1s are known to globally influence gene expression profiles, differentiation state, and proliferation capacity of early embryos and many types of cancer, although by mechanisms which remain unclear [26]. Thus far, the S/MAR-related function of L1s remains unexplored in conjunction with their expression status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the fact that mature spermatozoa are endowed with reverse transcriptase, Spadafora and associates have blocked its action, using the anti-retroviral drug Nevirapine, to discover that this caused an irreversible arrest of development up to the four-cell stage of mouse development. 31 They further demonstrated that reverse transcriptase inhibition caused a substantial reprogramming of gene expression in arrested embryos, involving both developmental and translational genes. 32 This suggests that endogenous retroviruses, or LINE type products, are playing an important role at the earliest stages of mammalian development.…”
Section: The Implications For Human Development and Normal Physiologymentioning
confidence: 99%
“…A fuller understanding of this HERV role, coupled with a deeper epigenetic understanding, is likely to contribute to new lines of therapy, including immunotherapy. 25,85 Part 5 of this series will examine the role of epigenetics and genomic duplications in health and disease. …”
Section: In Summarymentioning
confidence: 99%